Aktivitas Antioksidan Sediaan Nutraceutical Tablet Hisap Ekstrak Daun Ubi Jalar Ungu (Ipomoea batatas L.) Varietas Antin-3 - Dipahayu, Damaranie; Safira, Irma Adinda (Universitas Borneo Lestari, 2025)
Purple sweet potato leaf extract Ipomoea batatas L variety Antin-3 (Antin-3 leaf extract) is a source of natural antioxidants because of its high flavonoid and polyphenol content. This study aims to determine the effect of variations in binding components on the antioxidant activity of nutraceutical preparations of EDA3 lozenges. The binding material used is PVP K-30 with concentrations of 5% and 10% (F1; F2), both samples will be seen for their antioxidant activity using the DPPH method. From the study result, the extract obtained an average IC50 value in F1 of 24.1ppm ± 0.8; F2 of 63.4ppm ± 2.0; pure vitamin C was 10.1 ppm± 0.1. In the Independent T-Test statistical test, sig 2-tailed (0.00) <0.05 was obtained, which means that there is an effect of the binder on antioxidant activity with sig 2-tailed (0.00) <0.05. Antin-3 leaf extract lozenges with 5% PVP K-30 have been shown to have three times greater antioxidant activity (DPPH method) compared to Antin-3 leaf extract lozenges with 10% PVP K-30.